High Diversity of Leptospira Species Infecting Bats Captured in the Urabá Region (Antioquia-Colombia) (2021)
ABSTRACT: Leptospirosis is a globally distributed zoonotic disease caused by pathogenic bacteria of the genus Leptospira. This zoonotic disease affects humans, domestic animals and wild animals. Colombia is considered an endemic country for leptospirosis; Antioquia is the second department in Colombia, with the highest number of reported leptospirosis cases. Currently, many studies report bats as reservoirs of Leptospira spp. but the prevalence in these mammals is unknown. The goal of this study was to better understand the role of bats as reservoir hosts of Leptospira species and to evaluate the genetic diversity of circulating Leptospira species in Antioquia-Colombia. We captured 206 bats in the municipalities of Chigorodó (43 bats), Carepa (43 bats), Apartadó (39 bats), Turbo (40 bats), and Necoclí (41 bats) in the Urabá region (Antioquia-Colombia). Twenty bats tested positive for Leptospira spp. infection (20/206-9.70%) and the species of infected bats were Carollia perspicillata, Dermanura rava, Glossophaga soricina, Molossus molossus, Artibeus planirostris, and Uroderma convexum. These species have different feeding strategies such as frugivorous, insectivores, and nectarivores. The infecting Leptospira species identified were Leptospira borgpetersenii (3/20-15%), Leptospira alexanderi (2/20-10%), Leptospira noguchii (6/20-30%), Leptospira interrogans (3/20-15%), and Leptospira kirschneri (6/20-30%). Our results showed the importance of bats in the epidemiology, ecology, and evolution of Leptospira in this host-pathogen association. This is the first step in deciphering the role played by bats in the epidemiology of human leptospirosis in the endemic region of Urabá (Antioquia-Colombia).